Leadership Strategy Evaluation and Succession Planning in Preparing the Company’s Future Leaders - Nurinaya, Nurinaya; Marhumi, Sitti (Advances in Human Resource Management Research, 2025)
Purpose: This study explores the integration of leadership strategy evaluation and succession planning in preparing future organizational leaders. It investigates how organizations can evaluate the effectiveness of current leadership strategies and align them with long-term organizational goals to ensure sustainable leadership continuity. Research Design and Methodology: This research employs a qualitative systematic literature review (SLR) methodology to synthesize existing leadership strategy evaluation and succession planning research. The study examines key practices, challenges, and theoretical frameworks associated with leadership development and succession planning, drawing from recent studies published after 2018. Findings and Discussion: The findings reveal that organizations integrating leadership strategy evaluation with succession planning are better positioned to ensure leadership continuity. Effective leadership strategies focus on developing internal talent through structured training, mentorship, and job rotations. The study emphasizes the need for leadership strategies to be aligned with organizational goals, enabling future leaders to navigate long-term challenges effectively. Additionally, the research highlights the importance of overcoming challenges such as resistance to change and organizational culture in implementing effective succession planning. Implications: This research provides practical insights for organizations to align leadership development with succession planning, ensuring long-term organizational sustainability. It emphasizes the importance of developing internal leadership pipelines, creating mentoring systems, and integrating human resource policies with strategic goals. Organizations are encouraged to foster a culture of internal mobility and continuous leadership development to ensure seamless transitions and minimize operational disruptions.